2010
DOI: 10.1038/jcbfm.2010.72
|View full text |Cite
|
Sign up to set email alerts
|

Necrostatin Decreases Oxidative Damage, Inflammation, and Injury after Neonatal HI

Abstract: Necrostatin-1 inhibits receptor-interacting protein (RIP)-1 kinase and programmed necrosis and is neuroprotective in adult rodent models. Owing to the prominence of necrosis and continuum cell death in neonatal hypoxia-ischemia (HI), we tested whether necrostatin was neuroprotective in the developing brain. Postnatal day (P)7 mice were exposed to HI and injected intracerebroventricularly with 0.1 lL of 80 lmol necrostatin, Nec-1, 5-(1H-Indol-3-ylmethyl)-(2-thio-3-methyl) hydantoin, or vehicle. Necrostatin sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
197
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(208 citation statements)
references
References 41 publications
11
197
0
Order By: Relevance
“…A recent study found that Nmnat1 mediates its axonal protective effect in the presence of activated caspase-6 after tropic factor deprivation in dorsal root ganglion neurons (18). Interestingly, necrostatin, a small-molecule inhibitor of programmed necrosis (necroptosis), also fails to inhibit the activation of the caspase-3 pathways in animal models of neonatal brain injury (47) even though it provides significant protection in neonatal H-I and other mice models of acute injury (47)(48)(49). Whether the pathways activated by Nmnat1 and necrostatin overlap is unclear and will be an important area for future study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that Nmnat1 mediates its axonal protective effect in the presence of activated caspase-6 after tropic factor deprivation in dorsal root ganglion neurons (18). Interestingly, necrostatin, a small-molecule inhibitor of programmed necrosis (necroptosis), also fails to inhibit the activation of the caspase-3 pathways in animal models of neonatal brain injury (47) even though it provides significant protection in neonatal H-I and other mice models of acute injury (47)(48)(49). Whether the pathways activated by Nmnat1 and necrostatin overlap is unclear and will be an important area for future study.…”
Section: Discussionmentioning
confidence: 99%
“…Model of neuronal cell death in neonatal H-I initiated by NMDAmediated excitotoxicity. Excitotoxicity after neonatal H-I initiates necrosis and apoptosis as well as cell death that has features of both necrosis and apoptosis (3,10,21,46,47). Pan-caspase and caspase-3-specific inhibitors as well as overexpression of Bcl-XL and knockout of Bax significantly protect against neonatal H-I in rats and mice by blocking caspase-dependent celldeath pathways (6,23,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…At least for the kidney, it appears that necroptosis predominates over apoptosis and similar suggestions have been made in myocardial IRI (11,25). However, existing data that imply protection by interference with necroptosis in various in vivo models used the RIPK1 kinase inhibitor necrostatin (Nec)-1 to inhibit necrotic signaling (10,11,26,27). However, Nec-1 has recently been discussed to directly influence the immune system, besides its effects to block release of CDAMPs (28,29).…”
mentioning
confidence: 82%
“…Experiments using a specific necroptotic inhibitor, necrostatin-1 (Nec-1), and one of its derivatives, 7-chloroindolenecrostatin-1 (7-Cl-Nec-1), have confirmed that necroptosis is involved in the ischemic brain injury induced by focal cerebral ischemia and neonatal HI [14,77] . The protection effect of 7-Cl-Nec-1 is readily detectable, even when the compound is administered 6 h after the onset of cerebral ischemic injury [14] , at which point the administration of zVAD-fmk no longer decreases infarct volume [78] , indicating that necroptosis may participate in ischemia-induced delayed cell death.…”
Section: Autophagy Is a Response To Necroptotic Cell Deathmentioning
confidence: 99%